Twilight - Meyer, Stephenie, 1973- (New York : Little Brown & Co, 2008)
When seventeen-year-old Bella leaves Phoenix to live with her father in Forks, Washington, she meets an exquisitely handsome boy at school for whom she feels an overwhelming attraction and who she comes to realize is not wholly human.
First sight -- Open book -- Phenomenon -- Invitations -- Blood type -- Scary stories -- Nightmare -- Port Angeles -- Theory -- Interrogations -- Complications -- Balancing -- Confessions -- Mind over matter -- The Cullens -- Carlisle -- The game -- The hunt -- Goodbyes -- Impatience -- Phone call -- Hide-and-seek -- The angel -- An impasse -- An occasion.
"Megan Tingley books."
Includes excerpt and discussion guide.
Keywords: Vampires -- Fiction; High schools -- Fiction; Schools -- Fiction; Vampires -- Juvenile fiction; High schools -- Juvenile fiction; Washington (State) -- Fiction; Washington (State) -- Juvenile fiction